Prospects of biological and synthetic pharmacotherapies for glioblastoma. (3rd March 2020) - Altshuler, David B.; Kadiyala, Padma; Nuñez, Felipe J.; Nuñez, Fernando M.; Carney, Stephen; Alghamri, Mahmoud S.; Garcia-Fabiani, Maria B.; Asad, Antonela S.; Nicola Candia, Alejandro J.; Candolfi, Marianela; Lahann, Joerg; Moon, James J.; et al.
ABSTRACT: Introduction : The field of neuro-oncology has experienced significant advances in recent years. More is known now about the molecular and genetic characteristics of glioma than ever before. This knowledge leads to the understanding of glioma biology and pathogenesis, guiding the development of targeted therapeutics and clinical trials. The goal of this review is to describe the state of basic, translational, and clinical research as it pertains to biological and synthetic pharmacotherapy for gliomas. Areas covered : Challenges remain in designing accurate preclinical models and identifying patients that are likely to respond to a particular targeted therapy. Preclinical models for therapeutic assessment are critical to identify the most promising treatment approaches. Expert opinion : Despite promising new therapeutics, there have been no significant breakthroughs in glioma treatment and patient outcomes. Thus, there is an urgent need to better understand the mechanisms of treatment resistance and to design effective clinical trials.